MEDIATION IN TRADE MARK DISPUTES. THE BENEFITS OF MEDIATION IN THE BATTLES OF THE TRADE MARKS - Vassileva-Karapanova, Lyubka (Lex Electronica, 2023)
A well-recognized trademark is a valuable asset for its owner. It "sells" the goods or services for which it is used and builds a loyal customer base, giving the brand owner a competitive advantage in the market for those goods and services. The process of building and maintaining the reputation of a trademark requires considerable resources and persistence and is often surrounded by various disputes. The purpose of this article is to outline briefly, without claiming to be exhaustive, the specifics of trademark disputes and the benefits of mediation as a means of their resolution. A brief introduction to some basic trademark concepts is included to give an idea of the complexity of trademark disputes. Examples of trademark disputes resolved through negotiation or mediation are also included. As the relevant provisions of national trademark laws vary from country to country, the Regulation (EU) 2017/1001 on the European Union Trademark is used in the text as a reference law. It can be concluded that mediation in trademark disputes provides the parties with important advantages compared to traditional ways of resolving these disputes in adversarial administrative or judicial proceedings. Furthermore, instruments such as Directive 2008/52/EU and the Singapore Convention on Mediation enable the enforceability of settlement agreements resulting from mediation.